Comprehensive investigation of genetic variation in the 8q24 region and multiple myeloma risk in the IMMEnSE consortium - Campa, Daniele; Weinhold, Niels; Bugert, Peter; Goldschmidt, Hartmut (British journal of haematology, 2012)
Abstract Genome?wide association studies (GWAS) have shown that the 8q24 region harbours multiple independent cancer susceptibility loci, even though it is devoid of genes. Given that no GWAS data are currently available for multiple myeloma (MM), we tested the hypothesis that genetic variants in this region could play a role in MM risk. We genotyped 20 single nucleotide polymorphisms of 8q24 in 1188 MM cases and 2465 controls and found a statistically significant (P = 0·0022) association between rs2456449 and MM risk. These data provide further evidence that the genetic variability in the 8q24 region is associated with cancer risk, particularly haematological malignancies.
Gesehen am 11.04.2018